Mechanism study on organic ternary photovoltaics with 18.3% certified efficiency: from molecule to device. Issue 2 (21st January 2022) - Li, Yaokai; Guo, Yuan; Chen, Zeng; Zhan, Lingling; He, Chengliang; Bi, Zhaozhao; Yao, Nannan; Li, Shuixing; Zhou, Guanqing; Yi, Yuanping; Yang, Yang (Michael); Zhu, Haiming; et al.
Abstract : Our work presents a study on the working mechanism of ternary organic photovoltaic devices based on non-fullerene acceptors, focusing on the composition-dependent optoelectronic property variations in blend films and devices. Abstract : Multi-component organic photovoltaics (OPVs), e.g., ternary blends, are effective for high performance, while the fundamental understanding from the molecular to device level is lacking. To address this issue, we here systematically study the working mechanism of ternary OPVs based on non-fullerene acceptors (NFAs). With both molecular dynamics simulations and morphology characterization, we identify that when adding another larger band gap and highly miscible NFA, namely IT-4F or BTP-S2, into the PBDB-TF:BTP-eC9 blend, the NFAs undergo molecular intermixing selectively with BTP-eC9. This causes the composition-dependent band gap and charge recombination, and hence the composition-dependent V OC . While the charge recombination still dominantly occurs at the PBDB-TF:BTP-eC9 interface, BTP-S2 or IT-4F plays an auxiliary role in facilitating charge transfer and suppressing non-radiative decay. Interestingly, intermolecular end-group packing in the intermixed blend is improved compared to that in pristine films, leading to higher carrier mobility. These synergistic effects significantly improve the power conversion efficiency of the device to an outstanding value of 18.7% (certified value of 18.3%).